The Magnitude of the Health and Economic Impact of Increased Organ Donation on Patients With End-Stage Renal Disease. Issue 2 (December 2021) - Chen, Huey-Fen; Ali, Hayatt; Marrero, Wesley J.; Parikh, Neehar D.; Lavieri, Mariel S.; Hutton, David W.
Objectives. There are several approaches such as presumed consent and compensation for deceased donor organs that could reduce the gap between supply and demand for kidneys. Our objective is to evaluate the magnitude of the economic impact of policies to increase deceased donor organ donation in the United States.Methods. We built a Markov model and simulate an open cohort of end-stage renal disease patients awaiting kidney transplantation in the United States over 20 years. Model inputs were derived from the United States Renal Data System and published literature. We evaluate the magnitude of the health and economic impact of policies to increase deceased donor kidney donation in the United States.Results. Increasing deceased kidney donation by 5% would save $4.7 billion, and gain 30, 870 quality-adjusted life years over the lifetime of an open cohort of patients on dialysis on the waitlist for kidney transplantation. With an increase in donations of 25%, the cost saved was $21 billion, and 145, 136 quality-adjusted life years were gained. Policies increasing deceased kidney donation by 5% could pay donor estates $8000 or incur a onetime cost of up to $4 billion and still be cost-saving.Conclusions. Increasing deceased kidney donation could significantly impact national spending and health for end-stage renal disease patients.